Paradojas del duelo en el contexto colombiano (2013)
ABSTRACT: This article proposes a discussion around a Colombian social phenomenon, namely: the coexistence in everyday´s life of death and horror with different manifestations of festivities. The subject matter is approached from the concept of grief as central axis; this approach allows to hold its validity for the study of the aforementioned phenomenon in the Colombian context. The peculiar logic of grief in Colombia is discussed starting with a question: do paradoxes of grief in this country respond to new forms of normal grief, or are they rather expressions of old forms of complicated grief? The conclusion is that there exist in Colombia different mechanisms that keep the country in the silence of sorrow and in the paralysis of unelaborated grief.